MODERN APPROACHES IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE: METHODS AND CHALLENGES (International journal of artificial intelligence, 2025)
The article explores modern methods and approaches to teaching Russian as a foreign language. It highlights the importance of communicative and interactive techniques that focus on developing students’ practical speaking and listening skills. The paper also examines the role of information and communication technologies, mobile applications, and game-based learning in enhancing motivation and effectiveness. Special attention is given to individualized instruction, the use of authentic materials, and the integration of cultural elements. These innovations make learning Russian more engaging, accessible, and relevant to the needs of modern students in a globalized educational environment.